2017
DOI: 10.1007/s00280-017-3406-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel formulation of abiraterone acetate might allow significant dose reduction and eliminates substantial positive food effect

Abstract: The novel formulation might allow a 75% dose reduction with significant reduction of inter-individual variability. The negative food effect observed requires further investigations; however, elimination of the significant positive food effect could be adequate to negate the restriction of a food label.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…To keep the focus of the editorial, clinical pharmacokinetics comparison is only drawn between 200 mg DIB formulation versus 1000 mg Zytiga. In the two important parameters namely, peak concentration (C max ) and area under the concentration vs. time curve extrapolated to time infinity (AUC inf ), the values obtained for 200 mg DIB were 206 ng/mL and 408 ng.h/mL, respectively; relative to the values of 93 ng/mL and 513 ng.h/ mL, respectively, for the 1000 mg Zytiga tablets [5]. This clearly indicated that despite a 5-fold reduced oral dose of abiraterone acetate in DIB, the C max was almost 2-fold higher and AUC inf was 0.9-fold as compared to the respective values for the 1000 mg Zytiga reference product.…”
Section: Abirateronementioning
confidence: 97%
See 4 more Smart Citations
“…To keep the focus of the editorial, clinical pharmacokinetics comparison is only drawn between 200 mg DIB formulation versus 1000 mg Zytiga. In the two important parameters namely, peak concentration (C max ) and area under the concentration vs. time curve extrapolated to time infinity (AUC inf ), the values obtained for 200 mg DIB were 206 ng/mL and 408 ng.h/mL, respectively; relative to the values of 93 ng/mL and 513 ng.h/ mL, respectively, for the 1000 mg Zytiga tablets [5]. This clearly indicated that despite a 5-fold reduced oral dose of abiraterone acetate in DIB, the C max was almost 2-fold higher and AUC inf was 0.9-fold as compared to the respective values for the 1000 mg Zytiga reference product.…”
Section: Abirateronementioning
confidence: 97%
“…In order to address the issue of low solubility and large oral dose which impeded oral absorption of abiraterone acetate in clinical pharmacology studies, Solymosi et al [5] created amorphous nanoparticles using continuous flow precipitation technology used frequently for such difficult drug substances [6,7]. This creative adaptation of published technologies enabled novel abiraterone acetate formulation that improved dissolution rate along with enhanced solubility [5].…”
Section: Abirateronementioning
confidence: 99%
See 3 more Smart Citations